Molecular markers comparing the extremely simple body plan of dicyemids to that of lophotrochozoans: insight from the expression patterns of Hox, Otx, and brachyury - Kobayashi, Mari; Furuya, Hidetaka; Wada, Hiroshi (Evolution & development, 2009)
Because of their extremely simple body plan, dicyemids have long been the subject of phylogenetic controversy, regarding whether their body plan reflects their primitiveness or a degeneration from complex metazoans. Several studies have argued that the simple body plan of dicyemids are likely secondarily derived from higher lophotrochozoan animals, as a result of their endoparasitic, or endosymbiotic, lifestyle in the cephalopod kidney. To clarify the evolution of their simple body plan, we investigated the developmental expression patterns of three important regulatory genes, the central type Hox gene (DoxC), otx, and brachyury homologs in the dicyemid mesozoa, Dicyema orientale. DoxC was expressed in the trunk and tail of the asexually developing vermiform embryo, with clear anterior boundaries. Do-otx was expressed in the vegetal pole cells of the developing infusoriform embryos, suggesting that the invagination in infusoriform embryo is homologous to the gastrulation of other metazoans. Do-bra is expressed in the presumptive ventral cells, which are ventral to the opening of the urn cavity. The expression of Do-bra suggests that the urn cavity opening of the infusoriform embryo is comparable to the stomodium of trochophore larvae. These gene expression patterns provide molecular clues to trace the evolutionary history of degeneration in the dicyemid embryogenesis and life cycle from those of ancestral lophotrochozoan animals.